(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article provides a detailed examination of histamine, its role in the human body, and its medical significance. It explores the primary source of this compound—synthesized from the amino acid histidine—and its storage in mast cells. The article discusses histamine and its fractions (endogenous and exogenous), highlighting its involvement in various medical conditions such as allergies, asthma, and urticaria. Based on histamine’s effects in the body, the article also covers antihistamines and their therapeutic properties. Additionally, it presents information on various antihistamine drugs, their mechanisms of action, and the characteristics of first-, second-, and third-generation antihistamines. The article also provides important insights into foods that may cause histamine intolerance and their impact on the body.